Avaliação do Programa Mais Educação: a questão da inclusão educacional - Silva, Tânia Roberta da (2013)
This current research focus on the "Mais Educação” program relating the issues of educational inclusion. The goal is to investigate the beneficiary target’s point of view in relation to educational inclusion. The object of the study is analyzed indoors of EMEIF Delma Hermínia school, in the neighborhood of Jangurussu in Fortaleza, and the surrounding community, in order to comprehend the process of the program implementation in school and impressions of various agents which interact directly in this process, starting from the narratives of the same, within the methodological perspective of content analysis proposed by Bardin (2009). It reflects on the concepts of integral education and educational inclusion making an interface of the presented conceptions in the legal and theoretical marks which substantiate the proposal of the program with the concepts of various theories that approach the dialectic inclusion/exclusion. It is, therefore, an evaluative study with a qualitative approach, that seeks to contemplate the different factors pervade the daily school life of the program’s beneficiary target, the students, seeking to understand the meanings of the referred program for this audience, so to confront different ideas on the issue of educational inclusion enabling the reflection of it in the perspective of the learner’s own look.We conclude that although the “Mais Educação” program presents in its proposal positive aspects that can contribute to the process of educational inclusion, the daily routine of the program’s beneficiary target reveals other facets that putin "check" the proposal of the program related to the issue of educational inclusion . Our study brings these